(untitled) (Journal of Educational Sciences, 2023)
The formation of students’ scientific research skills is an important component of teaching genetics in higher educational institutions. Research skills the ability of students to search, creatively explore and evaluate useful information related to a particular topic. The formation of these skills includes conducting research, using critical analysis and forming hypotheses or solutions to a specific problem. The development of science and education is of great importance in the formation of intellectual potential. The article examines the DNA stamps of a model teaching method for the formation of research skills in the study of genetics, molecular biology for students of the specialty biology. A model is a representation of an idea, an object, a concept, a system. Working with the modeling method allows students to systematize, deepen and apply their knowledge in practice. In the genetics lesson, students conducted a study by modeling DNA replication, Nonsense, Missense, Frameshift mutations and the CRISPR mechanism. Modeling using DNA stamps increases students’ motivation, interest in the subject, facilitates evaluation, and also helps students remember modeling processes. Students’ knowledge was tested by means of questionnaires and interviews. As a result of the study, students became more interested in the subject and easily understood, modeling complex genetic processes. Key words: Genetics, molecular biology, modeling, research skills, DNA replication.